KESADARAN DAN KESIAPAN MENGHADAPI KEGAWATDARURATAN GIGI DI LINGKUNGAN SEKOLAH - Ulliana, Ulliana; Sulistiani, Silvia; Puspitawati, Yuli (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Dental trauma often occurs in school students. Teachers were the first people responsible for the initial handling of dental emergencies in the school environment. Teachers need to have good knowledge of handling dental emergencies. Proper management of dental emergencies during these events can improve the prognosis of dental trauma. The purpose of this service is to foster teachers’ awareness and readiness to deal with dental emergencies in the school environment. The service method consisted of several activities, namely training for 14 teachers, DMF-T examinations, toothbrushes, and dental immunizations, which were conducted on 157 students. The results of teachers' knowledge after being given training showed that the average teacher's knowledge score ranged from 78.75 to 92.86 with a p-value = 0.002, indicating that training on handling dental emergencies can increase teachers' knowledge. Students ' dental caries experience consisted of decay examination by 64%, missing by 33% and filling by 3%, and dental immunization by the application of CPP-ACP. This activity showed an increase in the participants' knowledge and was used as a manifestation of solutions to equip teachers regarding dental emergencies and their handling. It is hoped that teachers can apply their knowledge and act in the event of an emergency in the school environment.